First high resolution ro–vibrational analysis of C2HD3 in the region of the v12 band; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 218 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Kashirina N. V. Nadezhda Vladimirovna; Sydow C. Christian; Schiller M.; Blinzer T.; Bauerecker S. Sigurd (2018, 2018)
Title screen